Effect of Ridging on the Performance of Young Grapevines on a Waterlogged Soil - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
The effect of ridging on root development, vegetative growth and yield of young grapevines, cv. Chenin blanc/99R, was studied in a field trial on a soil naturally waterlogged during winter and early summer. Ridging tended to improve root efficiency as ell as general grapevine performance compared to unridged soil. There was no significant difference in vegetative growth of grapevines planted on 400 mm-high double row, 600 mm-high double row or 400 mm high single row ridges. Yield, however, decreased where the surface to volume ratios of double row and single row ridges were less than 0,6 and 1,0 respectively. This implied that excessively dry and warm soil conditions had occurred during ripening where the ridges were too large. Irrigation in combination with ridging resulted in significantly improved vegetative growth and higher yield compared to the unripped control treatment. Preliminary ripping of compacted subsoil to a depth of 550 mm tended to improve vegetative growth and yield of ridged as well as unridged treatments. Ridging had no significant effect on total soluble solids, total titratable acidity and pH of musts.